Antitumor DNA vaccination against the Sox2 transcription factor - Polakova, Ingrid; Duskova, Martina; Smahel, Michal (International journal of oncology, 2014)
As cancer stem cells (CSCs) are resistant to chemotherapy, radiotherapy and targeted molecular therapy, immunotherapy of tumors could be aimed at their elimination. Markers specific for CSCs have not been identified to date, but microarray analyses have shown that CSCs and embryonic stem cells use similar transcriptional programs, thus suggesting the production of shared transcription factors. In this study, we developed an experimental DNA vaccine against the transcription factor Sox2 that is important for self-renewal of stem cells and is overexpressed in numerous human cancers. The Sox2 gene was codon optimized for the expression in human cells, its sequences encoding two nuclear localization signals (NLSs) were mutagenized, and the sequence coding for the PADRE helper epitope was fused with its 5' terminus. While codon optimization did not increase Sox2 production and mutagenesis in NLSs only partially reduced nuclear localization of Sox2, the addition of the PADRE epitope was crucial for the enhancement of Sox2 immunogenicity. The antitumor effect was shown after immunization against mouse oncogenic TC-1/B7 cells derived from the lung cancer cell line TC-1 and characterized by high Sox2 production. Sox2-specific reactivity in an ELISPOT assay was further augmented by the depletion of regulatory T (Treg) cells, but this depletion did not enhance the antitumor effect. These data demonstrated the induction of immune responses against the Sox2 self-antigen, but did not confirm the usefulness of Treg depletion when combined with antitumor vaccination.
Keywords: imunizace; NIH 3T3 Cells; nádory plic; Cell Nucleus; Neoplastic Stem Cells; Cell Line, Tumor; Lung Neoplasms; regulační T-lymfocyty; buněčné jádro; T-Lymphocytes, Regulatory; Animals; lidé; ženské pohlaví; transkripční faktory SOXB1; Humans; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; SOXB1 Transcription Factors; nádorové kmenové buňky; nádorové buněčné linie; Mice; Female; DNA vakcíny; Immunization; Vaccines, DNA; buňky NIH 3T3